Akurasi Sensor TCS230 dalam Media Pembelajaran Bahasa Inggris - Aziz, As'ad Shidqy; Tri Kristianti (SMARTICS Journal, 2023)
English as an international language is expected to be able to make a real contribution to future superior generations who will take part in the international world. One of the right strategies for early childhood education in learning English is to listen and repeat. Thus, English Color Assistant learning media is needed to support early childhood English learning. The main components used to realize the tool include the TCS230 sensor and Arduino Uno. The results obtained from the design and manufacture of the tool prototype include the data generated by the sensor having a high level of precision, which is below 0.5. The accuracy of the tool in color reading is 100% when there is no distance between the tool and the detected media and 90% accuracy when there is a distance between the tool and the detected media.